Corporate Social Responsibility: Hasil Review Bibliometrik dan agenda penelitian di masa datang - Abbas, Dirvi Surya (JURNAL RISET AKUNTANSI TIRTAYASA, 2024)
This study uses bibliographic analysis to create a comprehensive research mapping on corporate social responsibility disclosure. Based on the Google Scholar and Scopus indexes from 2014 to 2023, this study analyzes the number of citations, publication trends, author collaborations, trending titles, trending author keywords, trending summaries, and countries of publication on corporate social responsibility disclosure, investigating changes in key factors, and investigating changes in key factors. research developments, and future research. This study uses a bibliometric analysis method. The research sample used was 1,500 articles using the keyword "Corporate Social Responsibility Disclosure". The articles used were sourced from journals indexed by Google Scholar and Scopus in 2014-2023, with the help of Publish or Perish (PoP) software. This bibliometric analysis uses VOSviewer (VV). The most citations according to statistics were in 2015, with a total of 976 citations. Related to publication trends, the least number of papers was published in 2016, which was 100 papers. The term 'Corporate Social Responsibility' is the most widely used keyword in this article. Corporate Social Responsibility Articles. There are three countries that associate Corporate Social Responsibility Disclosure with this study: 1) China, 2) America, and 3) Europe. The co-occurrence network visualization explains the network or relationship from one term to another in research in the field of Corporate Social Responsibility Disclosure for the period 2014-2023. The overlay visual represents keywords that indicate the year of publication, while the density visualization indicates research on a topic that is still very broad to be studied. The findings of this study indicate that it is important to be able to recognize the approaches and theories behind the development of Corporate Social Responsibility Disclosure in order to be able to determine the gradual nature of the aspects involved in it. This article calls for greater engagement among academics and researchers of Corporate Social Responsibility Disclosure to more explicitly consider how their research can contribute to the understanding of Corporate Social Responsibility. The limitation of this study is that it only uses the observation years 2016-2023. Further researchers are expected to be able to add observation years. In addition, this study has not explored the application of the literature used; Therefore, further researchers should develop this literature review with the help of other applications, such as Bliblioshiny or R